2016
DOI: 10.2298/tsci151210112h
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of an R744 liquid ejector for supermarket refrigeration systems

Abstract: This paper presents a numerical investigation of an R744 liquid ejector applied to a supermarket refrigeration system. The use of the liquid ejector enables the operation of the evaporator in a flooded mode and recirculates the R744 liquid phase, which improves the energy efficiency of the refrigeration system. The investigation was performed using two ejectors of different sizes installed in a multi-ejector block. The numerical model was formulated based on the homogenous equilibrium model and validated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…where u a (k) is the calculated snapshot based on the arbitrary parameter set k and f a (k) stands for vector of interpolation functions defined in Eq. (10). The implementation of RBF into the POD model reduces the dimensionality of ROM to the number of unknown parameters k. The unknown parameters are defined as the boundary conditions of the CO 2 two-phase ejector as follows:…”
Section: Pod-rbf Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…where u a (k) is the calculated snapshot based on the arbitrary parameter set k and f a (k) stands for vector of interpolation functions defined in Eq. (10). The implementation of RBF into the POD model reduces the dimensionality of ROM to the number of unknown parameters k. The unknown parameters are defined as the boundary conditions of the CO 2 two-phase ejector as follows:…”
Section: Pod-rbf Approachmentioning
confidence: 99%
“…This platform has been successfully used in several numerical investigations of the CO 2 ejector, i.e. parametrisation procedure of the R744 liquid ejectors [10], swirling of the motive and suction streams for ejector performance improvement [38], shape optimisation of the R744 twophase ejector [39] and numerical investigation of the multi-ejector module during single and parallel operation [40]. Therefore, the CFD results used to generate the hybrid ROM basis were obtained by use of the ejectorPL platform.…”
Section: Pod-rbf Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-ejector refrigeration system that was investigated by Haida et al (2016a) demonstrated that the application of ejectors provided significant COP improvements. Moreover, Haida et al (2016b) the liquid ejectors and performed a sensitivity analysis of the ejector shape on the ejector efficiency. However, in this study, only the vapour sucking ejectors were optimised.…”
Section: Ejector Designmentioning
confidence: 99%
“…As known, an ejector used as an expansion device in R744 transcritical systems, has improved the COP [4,5]. Several theoretical and experimental investigations have been performed for different configurations using ejector [6][7][8][9]. Design of the ejector is revised to work at refrigeration systems with R744.…”
Section: Introductionmentioning
confidence: 99%